Recent progress in the role of grain boundaries in two-dimensional transition metal dichalcogenides studied using scanning tunneling microscopy/spectroscopy - Hyo Won Kim (Applied Microscopy, 2023)
Abstract Grain boundaries (GBs) are one- or two-dimensional (2D) defects, which are universal in crystals and play a crucial role in determining their mechanical, electrical, optical, and thermoelectric properties. In general, GBs tend to decrease electrical or thermal conductivity, and consequently degrade the performance of devices. However, the unusual characteristics of GBs have led to the production of a new class of memristors with 2D semiconducting transition metal dichalcogenides (TMDs) and the creation of conducting channels in 2D topological insulators. Therefore, understanding the nature of GBs and their influence on device applications emphasizes the importance of GB engineering for future 2D TMD-based devices. This review discusses recent progress made in the investigation of various roles of GBs in 2D TMDs characterized via scanning tunneling microscopy/spectroscopy.